Seclusion, restraint, and involuntary medication in Finnish psychiatric care: a register study with root-level data. (31st July 2020) - Laukkanen, Emilia; Kuosmanen, Lauri; Selander, Tuomas; Vehviläinen-Julkunen, Katri
Abstract: Purpose: Despite potentially harmful effects, seclusion, restraint, and involuntary medication continue to be frequently applied in psychiatric care. These restrictive measures are often examined by means of registers, but homogeneous practices in the measurement and description seem to be missing. This nationwide register study aimed to examine the use of seclusion, mechanical and physical restraint, and involuntary medication in Finland. Material and methods: Root-level register data concerning the year 2017 were collected directly from 140 inpatient psychiatric wards within 21 organizations. The data were analyzed statistically. Results: In 2017, the most used restrictive measure in Finnish psychiatric wards was seclusion (4006 episodes), followed by involuntary medication (2187 episodes), mechanical restraint (2113 episodes) and physical restraint (1064 events). Similarly, the duration of seclusion episodes was longer than the duration of restraint episodes. Remarkable variation between wards in the use of seclusion, restraint and involuntary medication was observable. A negative binomial regression model (NB2) was used to analyze the associations between the use of restrictive measures and regional variables concerning demography, health, substance abuse, and socio-economic status, but reliable interpretations were impossible to generate. Conclusion: This study provides detailed and unique data on the use of seclusion, restraint and involuntary medication in Finland. Compared to previous national-level data, this study highlights the importance of collecting root-level data. Future research should use registries and describe the associations between the use of restrictive measures and ward-level factors, patient-level characteristics, and societal factors.